(untitled) (Global Journal of Science Frontier Research, 2021)
The research was set to investigate the morphological anatomical and phytochemical characteristics of Costus lucanusianus J Braun Schum of pan tropical family of monocots Costaceae in the Order Zingiberales It is amedicinal perennial herb which grows up to 3m in height without branches The glabrous stem is cylindrical greenish masked with brown leaf sheaths and hairs observed around the petiole base The petiolate leaves are lanceolate and large in spiral phyllotaxy measuring up to 25 10cm long and 7 5cm wide Region of leaf blade is pubescent and leaf apex is acute Flowers are in terminal clusters with cymose inflorescence The corolla is whitish with pinkish lips and deep yellowish throat Creeping rhizomes are present with fibrous root system The micro-morphological study revealed polygonal epidermal cells with tetracytic stomata and amphistomatic Anatomical study showed circular sections of spiral leaves with numerous scattered vascular bundles in the main stem The stem cortex is dominated with sclerenchyma while parenchyma occupied the ground meristem Pith is present in the root section which is surrounded with large vessels in ring form Phytochemical investigation revealed presence of flavonoids terpenoids steroids cardenolide and saponins